PENGARUH GOOD CORPORATE GOVERNANCE, CAPITAL EXPENDITURE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN: Studi Empiris Pada Perusahaan Consumer Non Cyclicals yang Terdaftar di BEI Tahun 2019-2021 - Alifia Aprizila Putri; Lilik Handajani; Robith Hudaya (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
For a company, the value of the company is very important because it reflects the overall performance that influences investors' assessment of the company's future prospects and becomes a benchmark for investors to invest in issuers. This study aims to determine the effect of Good Corporate Governance (GCG), Capital Expenditure (Capex), and profitability on firm value in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2021. Purposive sampling was used in the sample selection process so that a total of 41 companies were analyzed as samples. In this research, using the analytical method in the form of multiple linear regression analysis with the help of panel data utilizing the eviews 10 application. Based on the results of this study, it shows that Good Corporate Governance (independent commissioners, audit committees, institutional ownership) has no significant effect on firm value. Meanwhile, Capital Expenditure and profitability (ROE) have a significant influence on firm value. Keywords: Firm value, GCG, Capex, profitability